Стратегиско управување со проектите во фармацијата: улогата на надворешните специјализирани организации - Кикерков, Игор (Економски факултет, УКИМ, Скопје, 2013)
The pharmaceutical industry is facing countinuose rapid changes of its business practice and implemented strategy necessary for survival in terms of severe competition on the global market. The need of decrement of growing costs in this scientific and highly specialized area forces the engaged parties to rationalize their business activities without compromising the already achieved level of quality of their products. In the field of pharmacy and biotechnology the outsourcing or the cooperation with contract research organizations has been evidenced as the most attractive method in favor of cost rationalization and optimal usage of recourses available. The practice of engaging contract research organizations (CROs) has not been a novelty for the above mentioned industries, however it has been tremendously intensified during the last two decades. Using the services of the scientific and research, as well as of medical centers from the new market economies, the pharmaceutical companies managed to rationalize the usage of their own recourses, to eliminate time-gaps and to provide maximal rationalization of the duration of certain phases, by which they provided significant cuts of their costs and expenses. On the market as contract research organizations can act contract scientific and research organizations, academic medical centers and university hospitals, analytical laboratory centers, associated management organizations and institutions specialized for a particular market segment. Outsourcing has especially great importance for the pharmaceutical companies in the field of generic drug development. In the strategy of the pharmaceutical companies from the developed economies dominates the orientation of intensifying scientific research activities in the field of development of additional large number of new generics. These activities have been effectuated by implementing project management as practice performed by the contemporary business elite for decades. The project management applied in pharmacy is effectuated in five key steps: project definition, strategy creation, detailed planning, implementation and control and revision and learning. Including Central and Eastern European countries as full members of the EU, a part of the Balkan states, among which belongs our country as well, became attractive for conducting projects sponsored by pharmaceutical companies that originate from the EU. Being included in this type of projects our institutions are able to achieve not only gains in terms of additional financial inflow, but also of knowledge transfer on standardization and management of the terminal phase of generic drugs development up to the adopted western standards and practices. Up-to-date experience confirmed that also institutions of higher education in the western economies are able to comply with the role of single-window providers for different services for the needs of the pharmaceutical industry. Also, the Faculty of Medicine at the “Ss. Cyril and Methodius University” in Skopje has established a six-decade tradition of well developed system of cooperation with the domestic pharmaceutical industry. Lately it started to develop cooperation with foreign pharmaceutical companies, as well. For the successful accomplishment of this kind of research it is necessary to fulfill the following preconditions: presence of highly qualified and professional personnel; thorough knowledge of the national and international legislation and regulation on generic drugs; established standard operation procedures as required for conducting project activities ; excellent reputation on following dead lines up to the contract; quality project management and consulting role fulfillment; wellestablished infrastructure, capacity and technology under controlled working conditions; experience in performing different laboratory practices; quality datamanagement on contracted projects; reputation confirmed by cooperating clients’ satisfaction; etc. The preparation and the conduct of the research is a multitasking process where activities should be performed by a precisely defined schedule and established criteria.
Strategic project management in the pharmaceutical industry: the role of the contract research organizations
Докторска дисертација одбранета во 2013 година на Економскиот факултет во Скопје, под менторство на проф. д–р Бобек Шуклев.
Keywords: pharmaceutical industry, generic drugs, outsourcing, contract research organizations, project management